Validation of the Brazilian Portuguese version of the Venous International Assessment Scale and proposal of revision - Mayara Lopes; Julio César de la Torre-Montero; Maria Angélica Sorgini Peterlini; Mavilde da Luz Gonçalves Pedreira (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To validate the Brazilian Portuguese translation and analyze the cultural adaptation of the Venous International Assessment Scale. Methods: Observational study by employing the Delphi technique and an equivalence evaluation by experts. The results were analyzed using item scores and by content validity index calculations of item, scale, and universal agreement. Results: Three rounds of evaluation were necessary for consensus. Explanatory contents were incorporated into the original scale throughout the process, resulting in a new version: VIA Scale - Revised. This scale obtained a content validity index of 0.96 and a universal agreement of 0.78. In the cross-cultural adequacy analysis phase, a score of 0.77 was obtained. The majority (90.5%) of the participants judged the scale's decision support property as positive. Conclusion: The VIA Scale was validated and culturally adapted to the Brazilian Portuguese language, resulting in the VIA Scale - Revised (VIA-R).